The Use of Apatinib in Treating Nonsmall-Cell Lung Cancer: Case Report and Review of Literature - Ding, Lin (Medicine (Baltimore), 2016)
Apatinib is a novel tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor-2, which has been proved to be effective and safe in treating heavily pretreated patients with gastric cancer. The aim of the study was to explore the use of apatinib in treatment of nonsmall cell lung cancer and its side effects. We report 2 patients presented with advanced nonsmall-cell lung cancer, who received apatinib after failure in the first- or third-line chemotherapy. They are treated with apatinib in daily dose of 850 mg, 28 days per cycle. Favorable oncologic outcomes were achieved in the 2 cases after the treatment of apatinib. Patient I's progression-free-survival has increased to 4.6 months after palliative therapy of apatinib, whereas Patient II nearly 6 months. The common side effects of apatinib were hypertension and hand-foot syndrome; however, the toxicity of apatinib was controllable and tolerable. Apatinib may be an option for advanced nonsmall cell lung cancer after failure of chemotherapy or other targeted therapy. But that still warrants further investigation in the prospective study.